An investigation of the developmental neurotoxic potential of curcumol in PC12 cells. (21st November 2016) - Yu, Chunlei; Sun, Xiaojie; Niu, Yingcai
Abstract: Curcuma phaeocaulis Val. is a Chinese medicinal herb that is contraindicated during pregnancy for over a thousand years in China. The aims of the present study were to evaluate the effect of curcumol (one of the major components of C. phaeocaulis Val.) on neurite outgrowth and characterize the signal transduction pathways in PC12 cells. Curcumol significantly inhibited neurite outgrowth and cell proliferation, but did not cause cell death at a concentration of 450 μM in differentiated PC12 cells. In addition, curcumol evoked oxidative stress and it was indicated by an elevation in reactive oxygen species (ROS) and lipid peroxidation (LPO). Although PC12 cells exhibited inhibition of the differentiation into the acetylcholine (ACh) phenotype following 450 μM curcumol exposure, there was no significant alteration in net shift toward the ACh phenotype or tyrosine hydroxylase (TH) phenotype was observed. Neural cell adhesion molecule (NCAM)/focal adhesion kinase (FAK) but not extracellular signal-regulated kinases 1 and 2 (ERK1/2) signaling was repressed by curcumol exposure in differentiated PC12 cells. Curcumol does not affect calpain activity and nuclear factor-κB (NF-κB) DNA-binding activity. These findings suggest that curcumol might be a developmental neurotoxicant and NCAM/FAK signaling pathway may play an important role in curcumol-evoked inhibition of neurite outgrowth.